HUBUNGAN ISLAM DAN YAHUDI DALAM KONTEKS PLURALISME AGAMA - Zulkarnaini Abdullah (State Islamic University North Sumatra, 2009)
Abstract: The Relationship Between Islam and Judaism in the Context of Religious Pluralism. Religious pluralism has been an object of hot debates for decades, partly because of the recurring conflicts among different ‘religious’ communities. The present writer attemps to analyze the relations between Islam and Judaism in the contexts of religious pluralism, applying in the main Qur’anic exegesis method. The choice is interesting not only because of the close relation between the two in the history of Abrahamic religions but also in the context of the seemingly endless Israeli-Pelestine. The author believes that the way people read their holy book could contribute significantly to the effort of building harmony and peace.Kata Kunci: Islam, Yahudi, pluralisme agama